Europeanization of the Germany’s China Policy in Early 2020s: National Interests - Yu. Yu. Melnikova (Сравнительная политика)
The study aims to identify the significance of the European Union factor in shaping the foreign policy of the Federal Republic of Germany towards the People’s Republic of China in the early 2020’s. The research question stems from the existing contradiction between the economic interests of German states and business corporations on the one hand and the policy of the German government, which is increasingly distancing itself from China, on the other. It is hypothesized that Berlin’s shift to a confrontational strategy towards Beijing is largely due to “Europeanization” – the strengthening of centralization elements in European Union governance and the related adaptation of national models to the pan-European one. In the context of the “Europeanization” of foreign policy, supporting the existing trends rather than developing an alternative scenario contributes to preserving the leading role of Germany in the formation and implementation of the EU’s policy towards China. Thus, the study, in a certain sense, is a case study of the limits of autonomy of foreign policy of the integration associations’ member–states. Based on the bottom-up approach existing within the concept of “Europeanization,” the article provides a periodization of Germany’s policy towards China, taking into account the changes in the state of the EU ties with the latter. Four phases of German – Chinese engagements are proposed, namely 1993–2016, 2016–2019, 2019–2023 and 2023 until present. The comparison of the national and supranational levels of decision–making during these periods allowed us to demonstrate the full cycle of the “Europeanization” of Germany’s political course and once again emphasize the importance of the European Union in the formation of the policy of the state under study. Initially Germany presented its own norms of interaction with China to the EU level in order to ensure the most favorable conditions of cooperation with the latter; now it is adopting pan-European standards, adapting its national position to that of the European Union. The author’s conclusions are supported by the results of qualitative analysis of textual materials of the leading think–tanks in 2020–2024. The results of the study allow predicting further solidarization of Germany with the pan-European position and deterioration of German – Chinese relations.